Armazenagem de soja com controle da umidade relativa do ar de aeração - Gresele, Evertom Dutra (2020)
Agribusiness is essential for the national economy and as a source of food for the world. All this potential is possible due to the vast Brazilian territory and its technological advancement over the years. Producing is fundamental for maintaining the importance of agribusiness; and as part of the production process, storage is vital, since it is responsible for significant quantitative and qualitative losses of products. To mitigate these losses, the present study determined the technical breakdown and quality of soybean stored for more than six months in a silo with an aeration system and added moisture in the air. Two storage units, identical in their technical specifications, were used. However, only one had an air humidification system and monitoring. The stored product had its weight and quality determined before and after the storage period; the aeration, the advance of the cooling in the grain mass and the temperature difference between the environment and the incoming air in the grain mass were also monitored. The air humidification system is efficient in reducing technical breakage during the storage period, however, care must be taken in its use. Increased aeration opportunities and reduced aeration temperatures at low relative humidity are other advantages.